The Facility's Sanitation Requirements Canteen PT X Based on Regulation of KMK Number 1098, 2003 - Yayuk Octaliana Ningrum (JURNAL KESEHATAN LINGKUNGAN, 2018)
One of the efforts in maintaining food hygiene is to pay attention to hygiene and sanitation not only from food but also from the quality of the environment. The purpose of this study was to assess the suitability between food hygiene sanitation conditions with the related regulations that is KMK no. 1098 of 2003 on Hygiene Sanitation Requirements for Restaurants. This research was an observational research that lasted for 5 (five) weeks by doing observation, interview and literature study. The data obtained will be compared with KMK no. 1098 in 2003. Research shows that actual conditions that were not in accordance with regulation numb. 1098 of 2003 on Hygiene Sanitation Requirements for Restaurants, among others the meeting of walls and floors do not form a cone angle, the door that opens in without the protective gauze, washing facilities consist of 1 (one) tub, the condition of the waste bin open, poor ventilation, and food handlers do not use the media when in contact with food.